One-year results from a randomized comparative trial of targeted steroid injection via epidural catheter versus standard transforaminal epidural injection for the treatment of unilateral cervical radicular pain. Issue 9 (14th May 2021) - Conger, Aaron; Kendall, Richard W; Sperry, Beau P; Petersen, Russell; Salazar, Fabio; Cunningham, Shellie; Henrie, A Michael; Bisson, Erica F; Teramoto, Masaru; McCormick, Zachary L
Abstract : Objectives: The objective of this study was to evaluate the long-term effectiveness of catheter-directed cervical interlaminar epidural steroid injection with triamcinolone compared with cervical transforaminal steroid injection with dexamethasone for the treatment of refractory unilateral radicular pain. Design: Prospective, randomized, comparative trial. Methods: The primary outcome was the proportion of participants with ≥50% Numeric Rating Scale 'dominant pain' (the greater of arm vs neck) reduction from baseline. Secondary outcomes included ≥30% Neck Disability Index reduction and Patient Global Impression of Change response indicating 'much improved' or 'very much improved'. Results: Data from 117 participants (55.6% women; 52.3±12.5 years of age; body mass index, 28.2±6.5 kg/m 2 ) were analyzed. The proportion of participants who experienced ≥50% pain reduction at 1 month, 3 months, and 6 months has been previously reported. At 1 year, 61.2% (95% CI, 46.9% to 73.9%) of the catheter group compared with 51.9% (95% CI, 38.4% to 65.2%) of the transforaminal group reported ≥50% 'dominant' pain reduction (p=0.35). The proportion of participants who experienced ≥30% improvement in Neck Disability Index score was 60.4% (95% CI, 45.9% to 73.3%) and 47.1% (95% CI, 33.7% to 60.8%) in the catheter and transforaminal groups (p=0.18). Patient Global Impression of Change improvement was similar in both groups: 60.5% (95% CI, 44.2% to 74.8%) and 57.5% (95% CI, 41.7% to 71.9%) of the catheter and transforaminal groups reported being 'much improved' or 'very much improved', respectively (p=0.79). Conclusion: Both cervical catheter-directed interlaminar epidural injection and cervical transforaminal steroid injection were effective in reducing pain and disability in the majority of participants with refractory unilateral cervical radiculopathy for up to 1 year.